The lipid-soluble vitamins contents of some Vicia L. species by using HPLC - Emre, İrfan; Bahşi, Muammer; Genç, Hasan; Yılmaz, Ökkeş; Sahin, Ahmet (Pamukkale University, 2019)
In the present study, lipid-soluble vitamin compositions in the seeds of the Vicia L. taxa (V. ervilia (L.) Willd., V. cuspidata Boiss., V. peregrina L., V. cracca L. subsp. stenophylla Gaudin, V. mollis Boiss.& Hausskn., V. hybrida L., V. sativa L. subsp. nigra (L.) Ehrh. var. nigra L., V. sativa L. subsp. sativa (Ser.) Gaudin var. sativa, V. crocea (Desf.) B. Fedstch., V. noeona Reuter ex Boiss. var. noeona, V. narbonensis L. var. narbonensis) were determined by using HPLC. It was found that studied Vicia species apart from V. ervilia and V. cuspidata have highest ß-carotene contents, 1523,7±6,4 µg/g and 236,62±1,8 µg/g, respectively. Also, this study showed that V. ervilia and V. cuspidata have highest ?-tocopherol content. On the other hand, current study indicated that Vicia species have D3 vitamin contents between 13,8±0,62 µg/g and 50,5±2,13 µg/g. However, the ?-tocopherol, ?-tocopherol acetate, D2, K1, retinol and retinol acetate contents of studied Vicia L. species were lowest. © IJSM 2019.
Keywords: Fabaceae; HPLC; Lipid-soluble vitamins; Vicia L.